2017
DOI: 10.1039/c6nr07581a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of nose-to-brain delivery of nanoemulsions: cargoes but not vehicles

Abstract: The nose-to-brain pathway has been proven to be a shortcut for direct drug delivery to the brain. However, whether and to what extent nanoparticles can be delivered through this passage is still awaiting validation with evidence. In this study, nose-to-brain transportation of nanoparticles is tracked via fluorescence bioimaging strategies using nanoemulsions (NEs) as model carriers. Identification of NEs in biological tissues is based on the on → off signal switching of a new type of environment-responsive emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(75 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…SPC/cholesterol liposome formulations are widely found in the literature, and the particle size properties obtained are comparable to ours results [44,45]. The nose-to-brain passage of nanoemulsions has been studied through live imaging or ex vivo histological examination in rats after nasal administration by Ahmad et al [46]. This study demonstrated that nanoparticle size plays a determinant role, by directly influencing their in vivo fate.…”
Section: Preparation Of Liposomessupporting
confidence: 87%
“…SPC/cholesterol liposome formulations are widely found in the literature, and the particle size properties obtained are comparable to ours results [44,45]. The nose-to-brain passage of nanoemulsions has been studied through live imaging or ex vivo histological examination in rats after nasal administration by Ahmad et al [46]. This study demonstrated that nanoparticle size plays a determinant role, by directly influencing their in vivo fate.…”
Section: Preparation Of Liposomessupporting
confidence: 87%
“…Currently, efforts are concentrated on bypassing the very selectively permeable blood–brain barrier (BBB) and thereby delivering drugs directly into the brain . However, the efficacy of this route is yet to be experimentally proven . In comparison, most of the research into the buccal administration route is performed in order to increase retention time and to increase mucoadhesion so as to prevent the drug from being washed away by saliva .…”
Section: Therapeutic Nanomaterials—possible Routes Of Exposurementioning
confidence: 99%
“…Another possibility is the clearance of the nanomaterials via the lymph system. After extravasation of nanomaterials from the blood system, they face the dense interstitial space and ECM, a network of collagen, proteins, and elastic fibers that provide the structural integrity to the tissue . Diseases such as cancer and liver fibrosis reveal an altered ECM and an increased number of fibroblasts, which affect the penetration of nanomaterials through the tissue .…”
Section: Biological Barriersmentioning
confidence: 99%
“…Therefore, to address the low drug delivery problem, scientists are conducting experiments with nanoparticulate formulations like nanoemulsions, lipids, or polymer particles, which offer enhanced penetration and a longer residence time within the nasal cavity [156,[168][169][170][171][172][173][174][175][176] (Table 2). It has been found that 100 nm nanoemulsion particles penetrated the olfactory bulb and reached the brain to a small extent, whereas 900 nm particles could not penetrate the brain, which indicated that a particle size cut-off may be operational for the delivery of nanoformulations beyond the olfactory bulb [168]. A transformational effect is known to occur on the level of drugs detected in the brain following intranasal delivery when it is converted from solution to particulate formulation [177].…”
Section: Nanoparticles For Nose-to-brain Deliverymentioning
confidence: 99%